2019
DOI: 10.4103/abr.abr_106_19
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Melatonin on Anxiety and Pain of Tourniquet in Intravenous Regional Anesthesia

Abstract: Background:Melatonin has anxiolytic and potential analgesic effects. Several studies have indicated the sedative and anti-anxiety effects of melatonin when used as premedication before surgery. Hence, we assessed the efficacy of melatonin premedication in tourniquet-related pain and analgesia in patients receiving intravenous regional anesthesia (IVRA).Materials and Methods:Fifty patients undergoing elective hand surgery under IVRA were randomly divided into two groups (25 patients each) to receive either mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In heterogeneous clinical conditions, several recent trials have shown the potential of exogenous melatonin in the management of anxiety-related symptoms in somatic conditions with disturbances in sleep and circadian rhythms. In patients undergoing intravenous regional anesthesia, melatonin is associated with reduced anxiety, decreased tourniquet-related pain, and improved perioperative analgesia [69]. A Cochrane review concluded that melatonin reduced pre-operative and post-operative anxiety with an effect equal to benzodiazepines [70].…”
Section: Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…In heterogeneous clinical conditions, several recent trials have shown the potential of exogenous melatonin in the management of anxiety-related symptoms in somatic conditions with disturbances in sleep and circadian rhythms. In patients undergoing intravenous regional anesthesia, melatonin is associated with reduced anxiety, decreased tourniquet-related pain, and improved perioperative analgesia [69]. A Cochrane review concluded that melatonin reduced pre-operative and post-operative anxiety with an effect equal to benzodiazepines [70].…”
Section: Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…Concerning vaccines, exogenous melatonin acts as an adjuvant enhancing the response of CD8 + T cells in cancer vaccines (30,31) and vaccines employed against several pathogens in veterinary medicine (32). Melatonin increases the immune response to vaccines by increasing both CD4 + T cells and B cells that express IgG in peripheral blood.…”
Section: Melatonin As An Immunoenhancement Adjuvant In Anti-sars-cov-mentioning
confidence: 99%
“…For example, Shah et al (2016) compared anxiety relief under spinal anaesthesia in groups of people who were administered Propofol and Dexmedetomidine, respectively. Moreover, Abbasivash et al (2019) attempted to use Melatonin to mediate intraoperative anxiety in patients under spinal anaesthesia to avoid overuse of Propofol. However, despite their benefits, Dexmedetomidine and Melatonin used in both studies have a longer half‐life than Propofol and are related to slower recovery from anaesthesia (Abbasivash et al, 2019; Shah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Abbasivash et al (2019) attempted to use Melatonin to mediate intraoperative anxiety in patients under spinal anaesthesia to avoid overuse of Propofol. However, despite their benefits, Dexmedetomidine and Melatonin used in both studies have a longer half‐life than Propofol and are related to slower recovery from anaesthesia (Abbasivash et al, 2019; Shah et al, 2016). Thus, non‐pharmacological interventions should be considered to relieve intraoperative anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation